TAFSIR MAUDHU’I (TEMATIK) - Messi Ayuni; Muhammad Zaki; M Nabil Syaputra; Riska Sawitri (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study examines the method of Tafsir Maudhui (thematic interpretation) as a comprehensive approach to understanding the Qur'anic text by focusing on specific themes rather than individual verses. The research aims to analyze how thematic interpretation can provide deeper insights into Islamic teachings and facilitate the practical application of Qur'anic guidance in contemporary contexts. Employing a qualitative research design, this study utilizes library research and content analysis to examine classical and contemporary tafsir literature, including the works of prominent scholars who employed the maudhui approach. Data collection involves identifying relevant verses, classifying them according to themes, and analyzing interpretative patterns to uncover the rationale and methodology behind thematic exegesis. The findings indicate that Tafsir Maudhui not only enhances the coherence of Qur'anic messages but also offers a structured framework for understanding complex legal, moral, and social issues addressed in the Qur’an. The research demonstrates that this method bridges the gap between textual interpretation and practical application, providing a valuable tool for educators, scholars, and practitioners seeking to derive contextualized guidance from the Qur’an. Ultimately, Tafsir Maudhui contributes to a holistic understanding of Islamic teachings, promoting a thematic and integrated approach that strengthens both intellectual comprehension and spiritual reflection.